Perlindungan Hukum Terhadap Korban Penyalahgunaan Data Pribadi (Studi Kasus Penyalahgunaan NIK dalam Proses Pendaftaran Bacaleg di Lampung) - Putri Apriliani, Narisa; Rasji, Rasji (Universitas Ekasakti, 2023)
The misuse of personal data listed in the Population Identification Card (Kartu Tanda Penduduk or KTP) is a recurrent issue in Indonesia, including cases affecting residents of Lampung. Various internet users express dissatisfaction as their National Identification Numbers (Nomor Induk Kependudukan or NIK) are utilized without permission to support Jihan Nurlela, a legislative candidate (Caleg) for the Regional Representative Council of the Republic of Indonesia (Dewan Perwakilan Daerah or DPD RI). Despite the enactment of Law Number 27 of 2022 concerning Personal Data Protection (UU PDP), legal safeguards, whether in a preventive or punitive capacity, remain insufficiently effective. This article aims to scrutinize the issue, specifically examining the legal protection afforded to victims of personal data misuse as stipulated in UU PDP. The focus is directed toward the case of NIK misuse in Lampung, as well as efforts to enhance public awareness regarding personal data protection. The research methodology employed is normative-empirical, involving the examination of data from various sources, including relevant legal provisions, scholarly articles, and brief surveys conducted among the populace to gauge their awareness levels regarding personal data protection. Research findings indicate that legal certainty regarding the protection of victims of personal data misuse is yet to be optimally realized. Public awareness of the importance of personal data protection also remains incomplete due to specific internal and external factors. In the context of the NIK misuse case in the registration of Caleg in Lampung, reinforcement in the legal protection aspect is imperative. Recommendations encompass a call for the evaluation and updating of regulations by relevant governmental and institutional bodies, including the imposition of stricter sanctions for perpetrators of misuse. Additionally, law enforcement mechanisms need strengthening to ensure that every violation of personal data is justly and effectively penalized. To enhance public awareness, collaboration between the government, private sector, and non-profit organizations is advised to intensify educational campaigns.